The Teleological Ethics of Fakhr al-Dīn al-Rāzī - Shihadeh, Ayman (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
Using the most extensive collection hitherto of his published and unpublished writings, this volume provides a comprehensive, in-depth and interdisciplinary study of the ethical philosophy of al-Rāzī (1149-1210), a most outstanding and influential medieval philosopher-theologian. A complex picture emerges, across his philosophical, theological, ethical and juristic works, of a consistent and multi-layered ethical theory. Al-Rāzī departs from classical Ash'arī divine command ethics to develop both a consequentialist ethics of action, which seriously rivals Mu'tazili deontological ethics, and a perfectionist ethics of character. Within the latter framework, he sets out his later, teleological theory of prophecy. The volume includes the text, published for the first time, of one of al-Rāzī's latest and most fascinating works, Censure of the Pleasures of This World , which expresses pronounced moral and epistemological pessimism.